Observing Driver Distraction Behaviors at Intersections in Calabar Metropolis, Nigeria - Etika, Anderson A.; Edubi, Hycienth (Transactions on Engineering and Computing Sciences, 2026)
Driver distraction is increasingly recognised as a critical contributor to road traffic crashes, particularly at urban intersections where drivers are required to process multiple streams of information simultaneously. This study investigates the prevalence and patterns of driver distraction behaviours at selected intersections within Calabar Metropolis, Nigeria. Using a structured observational approach, driver behaviours were recorded across major intersections during peak and off‑peak periods over multiple days. Distraction types were categorised into mobile phone use, passenger interaction, eating or drinking, adjustment of in‑vehicle controls, external environmental distractions, and cognitive inattention. Descriptive and inferential statistical analyses were employed to examine variations in distraction behaviours across locations, time periods, and driver characteristics. Results indicate that mobile phone use and passenger interaction were the most prevalent forms of distraction, with higher occurrence rates observed during peak traffic periods. The findings underscore the safety risks posed by distracted driving at intersections and highlight the need for targeted enforcement, public awareness campaigns, and context‑specific traffic management interventions in Calabar Metropolis. This study contributes empirical evidence from a developing‑country urban setting and provides a basis for policy and engineering countermeasures aimed at improving intersection safety.